Chromosome numbers of Carex (Cyperaceae) and their taxonomic implications - Więcław, Helena; Kalinka, Anna; Koopman, Jacob (PloS one, 2020)
Counting chromosomes is the first step towards a better understanding of the karyotype evolution and the role of chromosome evolution in species diversification within Carex; however, the chromosome count is not known yet for numerous sedges. In this paper chromosome counts were performed for 23 Carex taxa from Armenia, Austria, the Czech Republic, and Poland. Chromosome numbers were determined for the first time in three species (Carex cilicica, 2n = 54; C. phyllostachys, 2n = 56; C. randalpina, 2n = 78), two subspecies (C. muricata subsp. ashokae, 2n = 58; C. nigra subsp. transcaucasica, 2n = 84) and two hybrids (C. ×decolorans, 2n = 74; C. ×walasii, 2n = 108). Among the taxa whose number of chromosomes had been known before, the largest difference was found in C. hartmaniorum (here 2n = 52) and C. aterrima subsp. medwedewii (here 2n = 52). A difference in the chromosome count was demonstrated for C. cilicica (2n = 54) versus the species of the section Aulocystis (2n = 30 to 40) and for C. tomentosa (2n = 48) versus the species of the section Acrocystis (2n = 18 to 38). The results of this study indicate that the position of C. cilicica in Aulocystis section may raise doubts. Attention was paid to the relationship between C. phyllostachys and taxa of the subgenus Carex section Gynobasidae.
Keywords: molekulární evoluce; Genetic Variation; chromozomy rostlin; Polsko; Poland; Chromosomes, Plant; genetická variace; Armenia; Austria; Evolution, Molecular; Carex Plant; Phylogeny; Arménie; Carex (rostlina); fylogeneze; Czech Republic; Rakousko; Česká republika